The Concepts Of Al-Zarnuji's Ethics In Islamic Education And Its Relevance For The Contemporary Era - Dinana, Muhammad Fahim; Nurhidin, Edi (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Education plays a significant role in shaping human behavior. Education in Islam encompasses academic pursuits of moral, ethical, and spiritual enlightenment. The current issues of moral decline within the family, school, and community are educational problems concerning moral and ethical education. This study describes al-Zarnuji's ethical concepts, as stated in his book Ta'lim al'Muta'alimis, and their relevance and applicability in contemporary education. This study is library research based on secondary data collected from documentation studies. It uses qualitative data described not by statistical data exposition but by word or descriptive explanation. The result shows that Al-Zarnuji's 13 (thirteen) chapters of his work had a unique view regarding ethics for the learning process. His educational ethics represent universal and rational ethics, which applies to contemporary education. The core value of this ethics is applicable beyond times and places, but its expression as a sociological phenomenon may be limited. It can be transformed according to a variety of circumstances. So, the expression of al-Zarnuji's ethics may vary according to places and times, schools and madrasahs or pesantrens, traditions, and culture. They are teachers, educational experts, and ulamas who should transform and adapt following different situations.